2012
DOI: 10.1016/j.jdiacomp.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on neuropathic symptoms, nerve function, and cutaneous innervation in people with diabetic peripheral neuropathy

Abstract: Although exercise can significantly reduce the prevalence and severity of diabetic complications, no studies have evaluated the impact of exercise on nerve function in people with diagnosed diabetic peripheral neuropathy (DPN). The purpose of this pilot study was to examine feasibility and effectiveness of a supervised, moderately intense aerobic and resistance exercise program in people with DPN. We hypothesize that the exercise intervention can improve neuropathic symptoms, nerve function, and cutaneous inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
280
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(317 citation statements)
references
References 26 publications
22
280
2
13
Order By: Relevance
“…However, if blood glucose was not controlled well, the peripheral neuropathy remained present in dominant hand. These findings were consistent with many previous observational studies [3][4][5][6][7][8][9]37].…”
Section: Discussionsupporting
confidence: 93%
“…However, if blood glucose was not controlled well, the peripheral neuropathy remained present in dominant hand. These findings were consistent with many previous observational studies [3][4][5][6][7][8][9]37].…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of exercise in exerting a similar effect in patients with diabetes who have signs and symptoms of DPN has yielded similar results. Patients with DPN who exercise regularly experience significant improvements in electrophysiological deficits and neuropathic symptoms, which is accompanied with increases in intraepidermal nerve fiber branching (Fisher et al, 2007;Hung et al, 2009;Kluding et al, 2012). In diabetic animals, exercise prevents myelin damage and attenuates changes in voltage-gated Ca 2ϩ channel function, thereby ameliorating electrophysiological deficits that occur in DPN (Selagzi et al, 2008;Shankarappa et al, 2011).…”
Section: E Exercise As a Nonpharmacological Therapy For Dpnmentioning
confidence: 99%
“…22 reported that, lack of physical activity was not directly associated with peripheral neuropathy while 23,24 found that there are association between lack of physical activity and early development of peripheral neuropathy. Also [24][25][26] observed that, physical activity was associated with lower rates of PN development. One potential strategy to delay or prevent the progression of diabetes to diabetic PN is regular physical activity.…”
Section: Discussion:-mentioning
confidence: 99%